2013
DOI: 10.5603/cj.2013.0137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and sex on echocardiographic left ventricular diastolic function parameters in patients with preserved ejection fraction and normal valvular function

Abstract: (Cardiol J 2013; 20, 5: 513-518)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
4
10
0
Order By: Relevance
“…Consistent with previous observations [34, 35], in the present study postmenopausal women had a 30% lower E/A and a 33% higher E/e’ compared to premenopausal women, indicative of reduced LV diastolic function. The present study extends previous work by providing evidence for oxidative stress as one potential mechanism underlying these observed differences.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous observations [34, 35], in the present study postmenopausal women had a 30% lower E/A and a 33% higher E/e’ compared to premenopausal women, indicative of reduced LV diastolic function. The present study extends previous work by providing evidence for oxidative stress as one potential mechanism underlying these observed differences.…”
Section: Discussionsupporting
confidence: 93%
“…One of the most important findings of this study is that the Septal E/e´ ratio was only predictive in male patients for an elevated LVEDP, whereas female patients lacked any significant correlation. This is in accordance with higher baseline E/ e´ ratios in female patients than in male patients [21][22][23]. A potential explanation for the latter finding is that the E/e´ ratio increases in female patients with increasing age disproportionately compared in male patients [12,23].…”
Section: Gender and Age Difference In Diastolic Functionsupporting
confidence: 79%
“…In addition to this, the E/e´ ratio was noticeably higher in the highest three age decades [20]. Finally, a relation was shown between E/e´ ratio and gender [21][22][23]. A study, published in 2013, showed that baseline E/e´ ratios in men were lower in men than in women [23].…”
Section: Gender and Age Difference In Diastolic Functionmentioning
confidence: 95%
See 1 more Smart Citation
“…Left ventricular (LV) filling and ejection patterns are critical determinants of the stroke volume in individuals with preserved systolic function. Aging is known to affect diastolic function by reducing myocardial elastic recoil which causes slow relaxation and eventually increased ventricular stiffness, but its effect on systolic function is not entirely clear . Changes of ventricular systolic and diastolic functions can easily be studied by Doppler echocardiography which has shown age‐related lengthening of the isovolumic relaxation time (IVRT) that correlate with the decrease in early diastolic LV filling velocity (E wave) and the increase in atrial systolic velocity (A wave) .…”
Section: Introductionmentioning
confidence: 99%